An Understanding of Mechanism-Based Approaches for 1,3,4-Oxadiazole Scaffolds as Cytotoxic Agents and Enzyme Inhibitors - Davinder Kumar; Navidha Aggarwal; Aakash Deep; Harsh Kumar; Hitesh Chopra; Rakesh Kumar Marwaha; Simona Cavalu (MDPI AG, 2023)
The world's health system is plagued by cancer and a worldwide effort is underway to find new drugs to treat cancer. There has been a significant improvement in understanding the pathogenesis of cancer, but it remains one of the leading causes of death. The imperative 1,3,4-oxadiazole scaffold possesses a wide variety of biological activities, particularly for cancer treatment. In the development of novel 1,3,4-oxadiazole-based drugs, structural modifications are important to ensure high cytotoxicity towards malignant cells. These structural modification strategies have shown promising results when combined with outstanding oxadiazole scaffolds, which selectively interact with nucleic acids, enzymes, and globular proteins. A variety of mechanisms, such as the inhibition of growth factors, enzymes, and kinases, contribute to their antiproliferative effects. The activity of different 1,3,4-oxadiazole conjugates were tested on the different cell lines of different types of cancer. It is demonstrated that 1,3,4-oxadiazole hybridization with other anticancer pharmacophores have different mechanisms of action by targeting various enzymes (thymidylate synthase, HDAC, topoisomerase II, telomerase, thymidine phosphorylase) and many of the proteins that contribute to cancer cell proliferation. The focus of this review is to highlight the anticancer potential, molecular docking, and SAR studies of 1,3,4-oxadiazole derivatives by inhibiting specific cancer biological targets, such as inhibiting telomerase activity, HDAC, thymidylate synthase, and the thymidine phosphorylase enzyme. The purpose of this review is to summarize recent developments and discoveries in the field of anticancer drugs using 1,3,4-oxadiazoles.